Targeting Neutrophil Extracellular Trap Formation: Exploring Promising Pharmacological Strategies for the Treatment of Preeclampsia - Leticia Lorena Hernández González; Laura Pérez-Campos Mayoral; María Teresa Hernández-Huerta; Gabriel Mayoral Andrade; Margarito Martínez Cruz; Edgar Ramos-Martínez; Eduardo Pérez-Campos Mayoral; Víctor Cruz Hernández; Ismael Antonio García; Carlos Alberto Matias-Cervantes; Miriam Emily Avendaño Villegas; Carlos Mauricio Lastre Domínguez; et al. (MDPI AG, 2024)
Neutrophils, which constitute the most abundant leukocytes in human blood, emerge as crucial players in the induction of endothelial cell death and the modulation of endothelial cell responses under both physiological and pathological conditions. The hallmark of preeclampsia is endothelial dysfunction induced by systemic inflammation, in which neutrophils, particularly through the formation of neutrophil extracellular traps (NETs), play a pivotal role in the development and perpetuation of endothelial dysfunction and the hypertensive state. Considering the potential of numerous pharmaceutical agents to attenuate NET formation (NETosis) in preeclampsia, a comprehensive assessment of the extensively studied candidates becomes imperative. This review aims to identify mechanisms associated with the induction and negative regulation of NETs in the context of preeclampsia. We discuss potential drugs to modulate NETosis, such as NF-κβ inhibitors, vitamin D, and aspirin, and their association with mutagenicity and genotoxicity. Strong evidence supports the notion that molecules involved in the activation of NETs could serve as promising targets for the treatment of preeclampsia.